Area postrema syndrome: an atypical presentation of primary Sjogren's - Tanwar, Sonam; Jadhav, Rahul; Oak, Jyotsna; Raut, Tushar (International Journal of Research in Medical Sciences, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune condition characterized by antibodies against serum aquaporin-4 (AQP4), primarily affecting the optic nerves and spinal cord. This case report sheds light on the diagnostic challenges of area postrema syndrome (APS) as the initial manifestation of Sjogren's syndrome, often misidentified due to its diverse symptomatology. APS, seen in 10% of NMOSD cases, manifests as persistent nausea, vomiting, and uncontrollable hiccups. Left untreated, APS can progress to optic neuritis and longitudinally extensive myelitis, emphasizing the need for early intervention with corticosteroid therapy and immunomodulators. NMOSD commonly coexists with other autoimmune diseases like Sjogren's syndrome and systemic lupus erythematosus. Recent evidence also highlights NMOSD's impact on peripheral organs, particularly skeletal muscles, with elevated creatine kinase levels during acute phases. Understanding the relationship between NMOSD and autoimmune diseases is vital for accurate diagnosis and management, especially in cases of seronegative NMOSD and recurrent attacks, emphasizing comprehensive clinical evaluations and a broader diagnostic approach.